Trees and Shrubs of Amritsar : A Pictorial Field Guide - Nagpal, Avinash kaur (Dehra dun india : M/s Bishen Singh Mahendra Pal Singh, 2024)
This book aims to document the diverse array of trees and shrubs, both indigenous and exotic, found in Amritsar city. These plants are growing along roadsides, in public gardens and parks, educational institutions, and residential, commercial, and industrial areas. While the walled city is highly congested, newer residential colonies on the outskirts are better planned with parks, contributing to a healthier and more beautiful environment. (3z(BTrees & Shrubs of Amritsar(3y (Bserves as a botanical guide for botany students and offers a delightful reading experience to educate plant lovers and the general public. The book provides pictorial representations of various trees and shrubs growing in the city, along with detailed information about their morphological features and photographs. This documentation aims to raise awareness among readers, whether botanists or common citizens. The book is particularly significant for botany students at all levels, from graduate to doctoral, as it includes the latest accepted botanical names (with etymology), IUCN conservation status, and detailed botanical descriptions. Written in accessible language, the book also includes vernacular and common names to cater to the interests of the general public.The book describes 100 species, with photographs provided for each species. Additionally, it documents the medicinal and other uses of each species. While the primary aim is to serve as a botanical guide for botany students, it also acts as a field guide for the general public, town planners, landscape officers, and others. The book helps readers identify and understand important morphological features, uses, and the flowering and fruiting times of the city$1 (Bs trees and shrubs. By covering basic information about different species of trees and shrubs found in Amritsar, many of which are also present in other parts of the country and the globe, this book has a broader relevance. It includes numerous exotic species, making it a valuable resource for readers worldwide.s
Includes references glossary index
Keywords: Plant biodiversity; Woody plants; Scientific names